Complicated family relationships, or about taxonomic problems in the family Pyrenomonadaceae (Cryptophyceae) - Solarska Magdalena; Adamski Michał; Piątek Jolanta (Oceanological and Hydrobiological Studies)
Cryptophytes, to which the Pyrenomonadaceae family belongs, are interesting organisms that occur almost all over the world and they are an important element of trophic chains in many ecosystems. The development of research methods and techniques, including electron microscopy and molecular studies, allowed for a better understanding of taxonomic relationships in this group of organisms. The Pyrenomonadaceae family currently includes three genera: Rhodomonas, Rhinomonas, and Storeatula, but their validity is being debated in the light of the latest data. The state of knowledge and the problems faced in the taxonomic revision of this family of cryptophytes are summarized in this article.